Prognostic Value of Platelet-to-Lymphocyte Ratio in Non-Muscle Invasive Bladder Cancer Patients: Intravesical Bacillus Calmette-Guerin Treatment After Transurethral Resection of Bladder Tumor - Wu, Ruicheng; Li, Dengxiong; Zhang, Facai; Bai, Yunjin; Wang, Xiaoming; Han, Ping (Frontiers in Surgery, 2022)
The objective of this study was to investigate platelet-to-lymphocyte ratio (PLR) in patients who underwent intravesical treatment for non-muscle invasive bladder cancer (NMIBC). A total of 197 patients who underwent intravesical Bacillus Calmette-Guerin treatment after transurethral resection of bladder (TURB) were included. We divided the patients into different groups according to the treatment stage before and during induction treatment as group 1 and group 2, and set the change value of PLR as the group 3. cut-off values of PLR were determined through receiver operation characteristics curves analysis. we found a significant difference in recurrence-free survival (PFS) and recurrence-free survival (PFS) between patients with high serum PLR and those with low serum PLR in group 1, as well as group 2. Cox multivariate analysis revealed that tumor number≥3, high grade, history of carcinoma in situ (CIS) were significant factors predicting RFS and PFS. Both the PLR values before and during induction therapy could be used as predictors for the progression and recurrence of NMIBC patients receiving BCG immunotherapy, and the PLR values after induction therapy have a stronger predictive power.